Interrelationship and cross‐field research in financial, human and capital markets - Grundey, Dainora (Technological and Economic Development of Economy, 2007)
“Interrelationship and cross‐field research in financial, human and capital markets”Technological and economic development of economy, 13(3), p. 177–178First Published Online: 21 Oct 2010